Mitochondrial permeability transition - Lemasters, John (Henry Stewart Talks, 2007)
Factors regulating opening of permeability transition pores, Models of permeability transition pore composition, Discrepancies of consensus model, Protein misfolding and the MPT, Rieske iron sulfur protein, Reye's syndrome, Ischemia/reperfusion and oxidative stress, Apoptosis, Mitochondrial autophagy (mitophagy), Necrapoptosis